Analisis Stilistika dan Nilai-Nilai Pendidikan Karakter pada Buku Puisi Amor Fati Karya Wayan Jengki Sunarta. - I Gusti Ayu Diah Citra Rasmi; I Gde Artawan; I Wayan Rasna (Universitas Nahdlatul Wathan Mataram, 2023)
The purpose of this research is to describe the stylistic elements contained in Amor Fati Poetry by Wayan Jengki Sunarta and describe the character education values contained in Amor Fati Poetry by Wayan Jengki Sunarta. This research is based on the theory of stylistics, poetry and character education values. This research is a descriptive qualitative research, which produces data in the form of written words, presented as it is without any treatment of the object under study and assisted by simple tables. Data collection in this research is done by literature or documentation method. The data obtained from the literature method was analyzed with descriptive-analytical techniques. Based on the analysis, there are eleven types of majas in the collection of Amor Fati Poems by Wayan Jengki Sunarta, namely personification, simile, periphrasis, pleonasm, prolepsis (anticipation), anaphora, metaphor, repetition, simile, mesodiplosis, and epanalepsis. There are thirteen character education values, namely religion, honesty, tolerance, hard work, creativity, independence, curiosity, love for the country, respect for achievement, friendship/communication, love of peace, social care, and responsibility. This indicates that not all of the eighteen character education values are found in Wayan Jengki Sunarta's Amor Fati.